The Effect of Product Innovation on Customer Loyalty (Survey of Samsung Phone Users in Indonesia) - Pepen Supriatna Supriatna; Agus Rahayu; Puspo Dewi Dirgantari (Dinasti Publisher, 2023)
In the digital era, Samsung is a brand that dominates smartphones. This South Korean brand is the number one Android phone manufacturer recognized for its capabilities globally. Even though Samsung has the highest market share, Samsung's market share has decreased. The low customer loyalty is allegedly the main cause of the decline in Samsung's market share. This paper aims to determine product innovation's effect on customer loyalty for Samsung cellphone customers in Indonesia. The research method in this scientific work is carried out quantitatively. The sampling technique used was nonprobability, with purposive sampling as the sampling technique. Meanwhile, the number of respondents was 100 people who live in Indonesia and are Samsung cell phone customers. While the data analysis technique used is simple linear regression analysis. The results of this study reveal a positive influence of product innovation on customer loyalty for Samsung cellphone customers in Indonesia.